2005
DOI: 10.1097/01.prs.0000149404.57087.8e
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction with the DIEP Flap or the Muscle-Sparing (MS-2) Free TRAM Flap: Is There a Difference?

Abstract: The advantages of breast reconstruction using the deep inferior epigastric perforator (DIEP) flap and the muscle-sparing free transverse rectus abdominis musculocutaneous (TRAM) flap (MS-2) are well recognized. Both techniques optimize abdominal function by maintaining the vascularity, innervation, and continuity of the rectus abdominis muscle. The purpose of this study was to compare these two methods of breast reconstruction and determine whether there is a difference in outcome. The study considered 177 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
159
3
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(178 citation statements)
references
References 28 publications
5
159
3
10
Order By: Relevance
“…[32][33][34] Our surgeons generally harvested DIEP and MS FTRAM flaps on either the medial or lateral DIEA branch through fascial incisions around the individual perforators using a fascia-sparing technique. DIEP flaps were raised by splitting the rectus abdominis muscle.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] Our surgeons generally harvested DIEP and MS FTRAM flaps on either the medial or lateral DIEA branch through fascial incisions around the individual perforators using a fascia-sparing technique. DIEP flaps were raised by splitting the rectus abdominis muscle.…”
Section: Methodsmentioning
confidence: 99%
“…(Figs. 2, 3) For patients with large breasts, evident ptosis and sufficient abdominal tissue, good options to consider would be the transverse rectus abdominis flap (as a pedicled or free myocutaneous flap) or the deep inferior epigastric perforator flap (based entirely on the (63,64), as with these flaps the reconstructed breast can resemble closely the native breast. However, this is not a good option for obese patients that present with high risk of fat necrosis and impaired wound-healing (11,65) or for patients with significant comorbidities that could increase the risk of complications.…”
Section: Delayed Breast Reconstructionmentioning
confidence: 99%
“…Two SIEA articles that were found after the initial search were also included (19,30). In summary, a total of 30 studies were used for the present analysis (five SIEA [ Table 1] [6,19,[28][29][30]) and 27 DIEP [ Table 2] [6,9,13,28,.…”
Section: Health Outcome Probabilitiesmentioning
confidence: 99%
“…A comparison of the muscle-sparing free TRAM flap with the DIEP found that there were no statistically significant differences in outcomes, but costs were not included in this analysis (9). However, previous cost-effectiveness studies (17,18) found that the introduction of techniques that caused less disruption of muscle and fascia were cost-effective in the Canadian health care system.…”
mentioning
confidence: 99%